Assessing Practice Teachers’ Culturally Responsive Teaching: The Role of Gender and Degree Programs in Competence Development - Manuel E. Caingcoy; Vivian Irish M. Lorenzo; Iris April L. Ramirez; Catherine D. Libertad; Romeo G. Pabiona Jr.; Ruffie Marie C. Mier (IAFOR Journal of Cultural Studies, 2022)
Culturally Responsive Teaching (CRT) weaves together rigor and relevance while it improves student achievement and engagement. The Philippine Department of Education implemented Indigenous People’s education to respond to the demands for culturally responsive teaching. Teacher education graduates are expected to articulate the rootedness of education in sociocultural contexts in creating a learning environment that recognizes respect, connectedness, choice, personal relevance, challenges, engagement, authenticity, and effectiveness. Practice teachers need relevant exposure and immersion to fully develop their competence in CRT. This scenario necessitates attention to assessing the competence of 191 practice teachers in CRT, correlating their competence across dimensions, and verifying the role of gender and degree programs in competence development. This investigation provides evidence on the role of gender in competence development toward culturally responsive teaching. Such competence is vital in practice teachers, especially because they are exposed to learners with diverse backgrounds during their teaching internship. This evidence informs supervising instructors in molding practice teachers.